Q:-solve this equation
![\frac{1}{3} x - 4 = x - ( \frac{1}{2} + \frac{x}{ 3} ) \frac{1}{3} x - 4 = x - ( \frac{1}{2} + \frac{x}{ 3} )](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B3%7D+x+-+4+%3D+x+-+%28+%5Cfrac%7B1%7D%7B2%7D+%2B+%5Cfrac%7Bx%7D%7B+3%7D+%29)
Answers
Answered by
5
Step-by-step explanation:
Q:-solve and verify the equation
_ _ _ _ _ _ _ _ _ _ _ _ _ _ _✍️
══════════XXX═════════════
cancelling 6( R.H.S) By 3 From L.H.S
CHECK:-
THEREFORE,L.H.S=R.H.S
VERIFIED✔️
══════════XXX═════════════
HOPE IT HELPS YOU..
_____________________
Thankyou:)
Similar questions